2016
DOI: 10.1371/journal.pntd.0005094
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of PD-1 Signaling Enhances Th2 Cell Responses and Aggravates Liver Immunopathology in Mice with Schistosomiasis japonica

Abstract: BackgroundMore than 220 million people worldwide are chronically infected with schistosomes, causing severe disease or even death. The major pathological damage occurring in schistosomiasis is attributable to the granulomatous inflammatory response and liver fibrosis induced by schistosome eggs. The inflammatory response is tightly controlled and parallels immunosuppressive regulation, constantly maintaining immune homeostasis and limiting excessive immunopathologic damage in important host organs. It is well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Strikingly, PD-1 + T H 17 cells are present in pulmonary fibrosis of distinct etiologies [chronic antigenic stimulation from microbial antigens (for example, sarcoidosis) (32), genetic alterations in the Src homology 2 domain–containing phosphotyrosine phosphatase-2 (Shp2) signaling pathway (for example, IPF) (33), or bleomycin- induced pulmonary fibrosis], suggesting that the PD-1/STAT3/T H 17 pathway may represent a point of immunologic convergence resulting in organ fibrosis. The presence of PD-1 + CD4 + and CD8 + T cell up-regulation in liver and skin fibrosis has also been reported (34). …”
Section: Discussionmentioning
confidence: 92%
“…Strikingly, PD-1 + T H 17 cells are present in pulmonary fibrosis of distinct etiologies [chronic antigenic stimulation from microbial antigens (for example, sarcoidosis) (32), genetic alterations in the Src homology 2 domain–containing phosphotyrosine phosphatase-2 (Shp2) signaling pathway (for example, IPF) (33), or bleomycin- induced pulmonary fibrosis], suggesting that the PD-1/STAT3/T H 17 pathway may represent a point of immunologic convergence resulting in organ fibrosis. The presence of PD-1 + CD4 + and CD8 + T cell up-regulation in liver and skin fibrosis has also been reported (34). …”
Section: Discussionmentioning
confidence: 92%
“…(14,20,21) Specific T cells become exhausted within the chronic inflammatory area of infected organs, thus contributing over the long term to the escape of viruses, parasites, or tumor cells from immune attack. (10,(22)(23)(24) Several key surface molecules, such as PDCD1, LAG3, and CTLA4, which are associated with T-cell exhaustion and the blocking of which may recover the T-cell function, have been recognized and are usually defined as "immunocheckpoints" or more simply "checkpoints." (11,25) In the present study, our results demonstrated that TIGIT plays a critical role in parasite immune escape by negatively controlling antiparasite T-cell immunity; they showed that blocking TIGIT decreased E. multilocularis growth in experimental animals while restoring T-cell immune effector function and thus highly suggested that blocking TIGIT could treat AE in future clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mice with schistosome and Litomosoides sigmodontis infection have indicated that Th2 hypo-responsiveness is not related to PD-1 and PD-L1 interaction [22,57,58]. However, other studies have suggested that PD-1 is necessary for the Th2 hyporesponsiveness during schistosome infection [19,59]. Our findings from the PD-L1 blocking experiment in vivo were consistent with the latter, as we observed that PD-L1 blocking not only enhanced the expression of IL-4 and Bcl6 in splenic CD4 + T cells but also increased the expression of Th2 transcription factor Gata3.…”
Section: Discussionmentioning
confidence: 99%